Investigating the Effective Components on Customer Lifetime Value of Dairy Products in Tehran - F. Vajdi Hokm Abad; H. Rafiee; A.H. Chizari; S. Yazdani; S.S. Hosseini (مجله اقتصاد و توسعه کشاورزی)
In contemporary marketing, maintaining and enhancing customer loyalty toward a company's products or services has become a primary focus. Among the factors influencing customer loyalty is ethical marketing, a field of applied ethics related to the principles governing behavior, advertising, and regulation in marketing. Over the past two decades, ethical consumerism has grown in importance due to increasing social and environmental concerns. This study examines the impact of ethical components on Customer Lifetime Value (CLV) for dairy product consumers in Tehran in 2023. A total of 710 questionnaires were completed, and the GWRFM method was employed to extract the necessary information for calculating CLV. The results revealed a high frequency of clusters with low lifetime value. In the subsequent phase, multinomial logit regression was utilized to analyze the effect of ethical components on CLV, highlighting the significant positive impact of adherence to industry regulations and acceptance of social responsibility. Therefore, it is recommended that stakeholders in the dairy industry assure customers of their compliance with regulations and social responsibility to elevate them to higher-value clusters and foster loyalty. By respecting ethical norms, a substantial portion of consumers of cheese, yogurt, and ayran products may transition toward becoming valuable customers in this sector.